Barriers to Renewable Energy Development on Brownfields. Issue 4 (7th August 2016) - Spiess, Thierry; De Sousa, Christopher
Abstract: Brownfields that are reused for the generation of renewable energy are called brightfields. This rapidly emerging idea advocates the combination sustainable site reuse and the generation of electricity from renewables. While programmes like the RE-Powering America's Land Initiative herald its benefits, academia knows but little of its barriers and challenges. This study aims to examine the technical/environmental, regulator/financial/institutional, and social barriers to this type of development, along with measures that may address them. The barriers and measures were predominately identified via a qualitative and quantitative survey sent to brightfield developers (experts), along with a review of case studies and the emerging brightfield literature. The study found that environmental/technical barriers only differ from 'conventional' renewable energy projects (e.g. on Greenfields) in the event of site contamination. The latter then is what makes brightfields unique and is the source for a myriad of challenges concerning risk and liability, which cause financial problems and investment hesitance. However, evidence conjectures that there is less contextual public opposition to brightfields compared to conventional renewable energy.